1978
DOI: 10.1007/bf00116910
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-to-gas phase transitions in two-dimensional quantum systems at zero temperature

Abstract: Two-dimensional systems o[ bosons and /ermions are studied at zero temperature by means of variational calculations. When viewed as a [unction of the quantum parameter 7q = he/me~r in the variational context, bosons are [ound to undergo a second-order liquid-to-gas transition, whereas, contrary to expectations, [ermions are found to undergo a first-order transition with a region in which liquid and gaseous phases can coexist. Although these results are qualitatively the same as those in three dimensions, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
61
3

Year Published

1980
1980
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 12 publications
6
61
3
Order By: Relevance
“…i) 2D clusters with N particles [9,10,12] are predicted to become unbound when the mass m reaches a critical value m (N ) * [7]. This critical mass is predicted to be universal, i.e., m (N ) * = m * [10], and to be the same for the corresponding homogeneous system [8,19]. ii) For a given system size, the ground state energies E N near threshold are predicted to change exponentially as the atomic mass m decreases [7,11].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…i) 2D clusters with N particles [9,10,12] are predicted to become unbound when the mass m reaches a critical value m (N ) * [7]. This critical mass is predicted to be universal, i.e., m (N ) * = m * [10], and to be the same for the corresponding homogeneous system [8,19]. ii) For a given system size, the ground state energies E N near threshold are predicted to change exponentially as the atomic mass m decreases [7,11].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…It was argued by Miller and Nosanow [21] that pure two-dimensional 3 He should be a gas down to absolute zero. In the 4 He medium, however, the OREP provides a mechanism by which the 3 He subsystem could undergo a gas to liquid transition.…”
Section: Resultsmentioning
confidence: 97%
“…Recently, Sato et al [11] found the G-L transition with ρ c0 ≈ 1 nm −2 in the heat-capacity measurements on the third layer of 3 He on graphite down to T = 1 mK. This was inferred from a linear ρ−dependence of γ, the coefficient of the leading T -linear term of C in the degenerate region, as well as a kink at γ ≈ γ ideal .…”
mentioning
confidence: 97%
“…Most previous theories based on the variational calculations [2][3][4], the diffusion Monte Carlo calculation [5] and the Fermi hypernetted chain method [6] support the absence of self-binding of 3 He in 2D. Indeed, no signature of the gas-liquid (G-L) transition was experimentally observed in the first and second layer 3 He on graphite down to T ≈ 3 mK and to areal density ρ = 1 nm −2 [7]. This is in sharp contrast to monolayer 4 He with smaller quantum parameter on graphite.…”
mentioning
confidence: 99%
See 1 more Smart Citation